ANALYSIS OF COGS CALCULATIONS USING THE FULL COSTING METHOD IN KYKA MSMEs: Analisis Perhitungan HPP Dengan Metode Full Costing Pada UMKM KYKA - Tantri risda; Dian Fahriani; Rif’atul Choiriyyah; Dewi Arum Lestari; Alifiana Rahmawati; Muhammad Raffi Mirza (TALI JAGAD JOURNAL, 2023)
Cost of Production is a number of costs incurred to process raw materials into finished products that are ready to be sold. There are 17 eating places that sell the best-selling crispy bananas in Sidoarjo. So, in order to remain competitive, KYKA MSME players must be able to create prices that are considered reasonable by consumers and of course do not cause losses by using appropriate calculations. Determining the Cost of Goods Production at KYKA MSMEs uses the full costing method in determining the selling price, because the full costing method takes into account all components of the production budget. The full costing method provides more accurate and precise calculation results, so it can be used to improve business at KYKA MSMEs. This research aims to find out how KYKA MSMEs calculate the cost of production. This research is a type of qualitative research. The results of calculating the cost of goods manufactured by MSME KYKA using the full costing method have a difference of 55,332 and 1,229.6 for each package. The research results show that by using the full costing method the price determination obtained is more precise and accurate.